Genotype analysis of partial growth hormone gene (GH891│MspI) in Pesisir cattle and Simmental-Pesisir crossbred cattle - Hartatik, T.; Putra, D. E.; Volkandari, S. D.; Kanazawa, T.; Sumadi, S. (Diponegoro University, 2018)
Growth hormone gene that controls metabolism and body size of animals and polymorphism of the gene is known related to performance of livestock. Identification of gene polymorphisms was important to get early information to determine genetic markers associated with economically desirable traits. Genetic mapping is one of important characterizations in the selection process. Pesisir cattle is one of local cattle in Indonesia that are reared in West Sumatera and have become adaptive to local environment. The present study aimed to identify the genotype of Growth Hormone gene (GH891│MspI) of the Pesisir cattle and crossbred Simmental-Pesisir cattle (designated as SimPes) and relationship between growth performance (body weight and body size). The present study was conducted to 30 blood samples consisted of 15 Pesisir cattle and 15 SimPes cattle. Body weight and body size were measured at 12-18 months of age. The Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method was used in this research. The results showed that there exist three variant genotypes (MspI-/-, MspI+/-, MspI+/+) and that allele frequencies of MspI- and MspI+ were 53.3% and 46.7%, respectively. Non-significant effect has found between GH’s genotype and growth traits (Body measurement and body weight) in both of breed cattle. In conclusion, three variant genotypes (GH891│MspI) in Pesisir and SimPes (Simmental x Pesisir) cattle population were found and no significant effect on growth trait performance.